A phytoremediation coupled with agro-production mode suppresses Fusarium wilt disease and alleviates cadmium phytotoxicity of cucumber (Cucumis sativus L.) in continuous cropping greenhouse soil. (May 2021) - Tang, Lin; Hamid, Yasir; Chen, Zhiqin; Lin, Qiang; Shohag, Md. Jahidul Islam; He, Zhenli; Yang, Xiaoe
Abstract: Cadmium (Cd) contamination and continuous cropping obstacle often coexist in greenhouse soil and seriously restrict cucumber production. In this study, hyperaccumulator Sedum alfredii Hance was intercropped with spring cucumber ( Cucumis sativus L.), then rotated with low accumulator water spinach and autumn cucumber under rational water regime, composited amendment was applied to soil before transplanting autumn cucumber. The results showed that, compared with conventional crop rotation system (Chinese cabbage and cucumber rotation), superposition management practice suppressed Fusarium wilt disease by 28.4 and 57.4% and increased yield by 35.2 and 383% for spring and autumn cucumbers, respectively. Meanwhile, photosynthetic characteristics, antioxidant system and fruit quality were significantly improved. Furthermore, this mode modified soil microbial community structure, enhanced soil enzyme activities, and simultaneously reduced soil total and phytoavailable Cd by 30.3 and 47.7%, respectively. These results demonstrated a feasible technical system to achieve phytoremediation coupled with argo-production in Cd contaminated greenhouse soil with continuous cropping obstacle and provided useful information for further revelation of interaction mechanisms between multicropping and comprehensive biofortification measurements. Highlights: Intercropping with S. alfredii was effective for suppressing cucumber wilt disease. Water regime and soil amendment facilitated crops to achieve phytoavoidation. Wilt disease inhibition was the cause of the phenotype and physiology improvement. Superposition measure exhibited utmost modification of soil property. Phytoremediation coupled with agro-production is a feasible technology.